Executive Dominance in the Ratification Process of Law Number 11 of 2020 Concerning the Omnibus Law on Job Creation - Primana, Hengky; Singka Subekti, Valina (Journal of Law, Politic and Humanities, 2025)
This study examines the formation and implementation of Law Number 11 of 2020 on Job Creation in Indonesia, which aims to simplify regulations related to investment and labour. Using a normative juridical approach, this study analyses the formal, material, and implementation aspects of the law. The results reveal significant challenges in the legislative process, including the dominance of executive power, limited public participation, and lack of transparency. The strong coalition of government-supporting parties in parliament enabled the accelerated passage of the law, but this raised concerns about the legitimacy of the law and its ability to balance business, labour and environmental interests. The research concludes that the legislative process reflects fundamental imbalances in Indonesia's political and legal systems, emphasising the urgency of systemic reforms to strengthen public participation, increase transparency, and restore the balance of power between the executive and legislature. Addressing these issues is critical to strengthening the foundations of democracy and ensuring better governance in Indonesia.